Analyzing the External Environment in Business Strategy: PESTEL, Porter’s Five Forces, and the Identification of Opportunities and Threats - Liza Isma Kurnia; Etria Marsa Angela; Wiza Kurniawati; Tuti Andriani; A. Budi Waluyo; M Hazel Alfarizi; Kuswanto Kuswanto; Ahmad Soleh; Sri Wahyuni (The Future of Education Journal, 2026)
Rapid changes in the global economy and technological disruption require companies to continuously adapt to a dynamic external environment. This article aims to comprehensively examine the use of PESTEL, Porter’s Five Forces, and SWOT methods in business strategy analysis in Indonesia over the last five years. Using a Systematic Literature Review (SLR) approach, articles published between 2021 and 2026 were collected from Google Scholar, SINTA, and Garuda databases, with a total of 25 articles analyzed. The main findings of this review indicate that although PESTEL, Porter’s Five Forces, and SWOT remain relevant, these methods are often applied separately without adequate integration. This study highlights the need for a more holistic and integrative approach in analyzing external factors that influence business strategies. The article suggests that companies should combine these three methods to obtain a more comprehensive perspective and achieve sustainable competitive advantage.